Immunomodulatory activity of Lactobacillus rhamnosus strains isolated from goat milk: Impact on intestinal and respiratory infections - Salva, Maria Susana (2010)
The immune stimulation induced by Lactobacillus rhamnosus CRL1505 (Lr05) and L. rhamnosus CRL1506 (Lr06) on the resistance to infection with an intestinal pathogen (Salmonella typhimurium) and a respiratory pathogen (Streptococcus pneumoniae) was studied in swiss-albine mice experimental models. The cytokine profiles that induced the innate and specific immune response in both infectious processes were investigated. Both strains were able to improve resistance against the intestinal pathogen. Only Lr05 was able to induce a significant decrease in the number of S. pneumoniae in the lung, prevent its dissemination into the blood and induce a significant increase in Th1 (INF-γ) and Th2 (IL-6, IL-4 and IL-10) cytokine levels in the bronchoalveolar lavages (BAL). The changes in the cytokines profiles in BAL were associated with an increase in the number and activity of phagocytic cells and with the increase in specific antibodies in serum and BAL, which would explain the increased resistance to the challenge. The administration of Lr06 did not induce significant effects at the respiratory mucosal level. The results described in the present paper showed that certain LAB strains can share certain functional properties, although some of them can perform a functional role better than others, so that it is important to perform careful studies on specific strains, according to their therapeutic use.